Online workshop as a telehealth modality: An experience with college students with academic performance anxiety (Research, Society and Development, 2022)
The study aims to describe a telehealth program to coping COVID-19 pandemic, regarding to enhance social skills repertoire of college students with anxiety of performance. Participants were 24 college students from an university of State of São Paulo. Measures pre and pos-test were collected by an online questionnaire that investigate sociodemographic data, academic engagement, anxiety of performance, social skills and academic performance. The project was composed by eight weekly group meetings. Seven groups composed of three to four participants were organized. The eight meetings aimed to strengthening the skills of discrimination of physical indicators, behavioral and academic contexts related to performance anxiety; alternative behaviors to procrastination; problem-solving skills; Social Communication Skill applied to the academic context; Assertiveness Social Skill applied to the academic context; relaxation training; diaphragmatic breathing training; stimulus control and seminar presentation. As contributions of this study, the following stand out: a) the description of evaluation instruments, evaluation stages and processes involved in the dissemination of the program; b) presentation of all the topics covered in the telehealth modality; c) description of the adaptation of behavioral techniques to difficulties related to the academic context; d) the presentation of resources for the telehealth modality.